2015
DOI: 10.1118/1.4903286
|View full text |Cite
|
Sign up to set email alerts
|

HDR 192Ir source speed measurements using a high speed video camera

Abstract: The source maintains its speed even for the short interdwell distances. Dose variations due to the transit dose component are much lower than the prescribed treatment doses for brachytherapy, although transit dose component should be evaluated individually for clinical cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
(19 reference statements)
4
19
0
Order By: Relevance
“…Some clinics do not accept treatment plan dwell times shorter than 0.5 s due to the time it takes for the source to move between dwell positions (transit time) [61,62]. In addition, in modern afterloaders, the minimum dwell time depends on the distance between dwell positions [63].…”
Section: Dwell Time Measurementsmentioning
confidence: 99%
“…Some clinics do not accept treatment plan dwell times shorter than 0.5 s due to the time it takes for the source to move between dwell positions (transit time) [61,62]. In addition, in modern afterloaders, the minimum dwell time depends on the distance between dwell positions [63].…”
Section: Dwell Time Measurementsmentioning
confidence: 99%
“…It cannot be expected from hospitals to perform measurements to determine the instantaneous source speed profiles, as this requires high-speed cameras [60]. In order to be able to determine the transit dose component with high accuracy, accurate measurement of the source acceleration and speed profiles should be incorporated into treatment planning systems or provided by the afterloader manufacturer.…”
Section: Testmentioning
confidence: 99%
“…As an example, Varian Medical Systems (Palo Alto, CA) implemented a camera-based QA device (CamScale) to the Bravos afterloading system released in 2018 [25,26], which is not time resolved but already allows to easily perform multiple dwell position measurements and system recalibration when necessary (more on this topic in section 4.5.1). Studies have shown that the source cable movement can be measured using regular video cameras [27][28][29] and high speed cameras [25,30] . Although such techniques are not practical for daily QA, the latter offers a precise and accurate method to evaluate dwell positions, dwell times and source speed profiles, which can be used to evaluate transit time dosimetry.…”
Section: Advanced Treatment Workflow Methodsmentioning
confidence: 99%
“…The experimental setup adopted for the measurements was based on the work of Fonseca et al [30]. A transparent source step viewer QA device (model GM11008720 Record dummy and source *The reference settings adopted for the high-speed camera experiments were the standard settings offered by the system when a new plan is created: flexible applicator, transit time correction enabled, first dwell position at the tip of the channel, no distal correction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation